2003
DOI: 10.1046/j.1445-5781.2003.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of dizygotic triplet pregnancy following conventional in vitro fertilization

Abstract: The mechanism of monozygotic multifetal pregnancy and its association with assisted reproductive technology are uncertain. This report presents two cases of dizygotic triplet pregnancy after the transfer of three embryos in utero. The incidence of monozygotic twinning following assisted conception procedures is higher than in the general population. Zonal manipulation may be a major factor in the increased incidence of monozygotic twinning. As both cases followed the conventional in vitro fertilization (IVF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…In multiple embryo transfer, if one embryo results in monozygotic twinning and another embryo is also implanted, then a dizygotic triplet pregnancy or higher‐order multiple pregnancy occurs 14–19 . Alikani et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In multiple embryo transfer, if one embryo results in monozygotic twinning and another embryo is also implanted, then a dizygotic triplet pregnancy or higher‐order multiple pregnancy occurs 14–19 . Alikani et al .…”
Section: Discussionmentioning
confidence: 99%
“…In multiple embryo transfer, if one embryo results in monozygotic twinning and another embryo is also implanted, then a dizygotic triplet pregnancy or higher-order multiple pregnancy occurs. [14][15][16][17][18][19] Alikani et al reported that another embryo was also implanted in 63% of cases of monozygotic twinning. 7 At our clinic, of the 10 cases of monozygotic twinning following ART, another embryo was also implanted in five cases, producing dizygotic triplets.…”
Section: T He Incidence Of Monozygotic Twinning In Naturalmentioning
confidence: 99%